2014
DOI: 10.1016/j.euroneuro.2013.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Social interaction and social withdrawal in rodents as readouts for investigating the negative symptoms of schizophrenia

Abstract: Negative symptoms (e.g., asociality and anhedonia) are a distinct symptomatic domain that has been found to significantly affect the quality of life in patients diagnosed with schizophrenia. Additionally, the primary negative symptom of asociality (i.e., withdrawal from social contact that derives from indifference or lack of desire to have social contact) is a major contributor to poor psychosocial functioning and has been found to play an important role in the course of the disorder. Nonetheless, the pathoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(67 citation statements)
references
References 153 publications
2
64
1
Order By: Relevance
“…Although we performed the social interaction test under non-anxiogenic conditions (Wilson and Koenig, 2014), the lack of pro-social effect of diazepam in control animals (Fig. 2C) might appear surprising (Costall et al, 1991; File and Seth, 2003).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we performed the social interaction test under non-anxiogenic conditions (Wilson and Koenig, 2014), the lack of pro-social effect of diazepam in control animals (Fig. 2C) might appear surprising (Costall et al, 1991; File and Seth, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…by habituating animals to the arena and changing light conditions) to minimize the contribution of anxiety to the behavioral outcomes (Wilson and Koenig, 2014). Nevertheless, even under non-anxiogenic conditions, we cannot rule out that anxiety might still contribute to social withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, efforts are being made to improve its study in rodent models, though this remains a difficult task. Most work has focussed on social recognition, and various ways 30 of manipulating social interaction, itself a complex construct (Millan and Bales, 2013;Wilson and Koenig, 2014). In fact, fully-fledged social cognition (theory of mind and emotional processing) is probably not present in rodents underpinning the quest for alternative species for its study (Brune et al, 2006;Millan et al, 2012).…”
Section: Enriching the Repertoire Of Behavioural Readouts: Integratinmentioning
confidence: 98%
“…[7,24]. Cognitive appraisal, which is the mean human beings use subconsciously to regulate emotions before expressing them, in order to deliver a reaction of adequate level, has been observed to be less frequently used by schizophrenic patients [2,19].…”
Section: Social Cognitive Impairment In Schizophreniamentioning
confidence: 99%
“…Experimental models have shown that psychotic subjects seek social withdrawal, which is associated with altered neural pathways and receptors [5,9,16,17]. Patients with schizophrenia often find themselves being unable to recognize facial expressions or misunderstanding comments, even having trouble assessing whether someone is addressing them or not, and they progressively become socially isolated [2,18,19]. As such, social impairment has a stronger impact on quality of life than non-social impairment [2,20].…”
Section: Introductionmentioning
confidence: 99%